the ANALYSIS OF POWER QUALITY INDICATORS IN LIGHT INDUSTRY ENTERPRISES: ANALYSIS OF POWER QUALITY INDICATORS IN LIGHT INDUSTRY ENTERPRISES - To‘xtashev, Alisher; Kadirov, Kamoliddin; Xoldorov, Botir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In light industry enterprises, electricity consumption and its quality indicators directly affect production efficiency and product quality. This article proposes a new methodology for analyzing and calculating the quality of electricity, in which the production process is divided into interconnected blocks, and specific energy consumption and quality parameters are studied separately for each block. The study uses mathematical models and nomograms and experimental data to determine the relationship between energy consumption modes and quality indicators. The results show that the method of dividing into blocks reduces the difference between real and calculated indicators to 2-5%, which provides high accuracy. It is also proven that a decrease in the quality of electricity leads to additional losses in technological processes and the need for optimization measures to increase energy efficiency. The proposed method serves as a practical solution for improving energy management and ensuring environmental sustainability in light industry enterprises.